Old/New Subduction Zone Paradigms as Seen From the Cascades - Leeman, William P. (Frontiers in Earth Science, 2020)
This paper briefly reviews the magmatic manifestations of volcanic arcs, and aspects of how such magmas form. Common concepts about ‘how subduction zones work’ are reassessed – with particular emphasis on the atypical Cascades volcanic arc. This arc is associated with perhaps one of the warmest modern subduction zones, with accelerated slab dehydration and low flux of slab-derived fluids compared to most others. With minimized leverage of fluids, other aspects of arc magmatism become more evident. We see multiple distinct basaltic magma types, all represented by relatively primitive high-MgO end members that allow assessment of their conditions of formation. Dominant types include two distinct intraplate varieties: low-K tholeiite with similarities to MORB and another variety with affinities to many ocean island basalts. In addition, there is a spectrum of more typical calcalkalic basalts that range to fairly alkali-rich compositions (absarokites) as well as high-Mg basaltic andesites. These magma types are variably present throughout much of the arc and all are present coevally in a transect paralleling the Columbia River. Their complex spatial distributions may in part reflect along-strike differences in tectonic controls and/or dynamics of mantle convective flow. The Cascades arc is broader than most other arcs, with significant basaltic volcanism locally in frontal and back arc regions. Prominence of basaltic magmatism has emerged since the late Miocene, and may be related to changes in the regional tectonic regime over time. These mafic magmas provide energy to drive melting in the crust, and perhaps in the lithospheric mantle, that feeds the more prominent stratovolcanoes distributed along the arc axis. Thermobarometry of the most primitive basalts implies unusual relations between depth and composition, as well as conflicting views regarding melt generation. Some traditional interpretations concerning [1] the conditions of magma formation, [2] the role of subducting oceanic plates (± sediments) in forming volcanic arc magmas, and [3] the nature of magmatic source domains in general appear to be inconsistent with current observations to some degree. These topics are reviewed and their implications assessed regarding physical and tectonic aspects of subduction zones.